On the presence of Scinax pedromedinae (Henle, 1991) (Amphibia: Anura: Hylidae) in Amazonian Brazil and northern Peru - Hoogmoed, Marinus Steven; Avila-Pires, Teresa Cristina Sauer (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
We report the presence of Scinax pedromedinae in northern Peru, near the point where the borders of Peru, Brazil, and Colombia meet (660 km northeast of Pucallpa and 900 km N of Puerto Maldonado), and in the Estação Ecológica Mamirauá in central Amazonas State, Brazil (1,200 km NE of Pucallpa, 1,100 km NNE of Puerto Maldonado, and 600 km E of the northern Peruvian locality reported here). These new records suggest a continuous distribution of this species in the western Amazon Basin, in eastern Peru, western Brazil, and northern Bolivia.